Policy diffusion and the competition for mobile resources - Andrea Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Reforms are often introduced in one region and afterwards adapted by other regions. This paper analyzes a model where policy diffusion can be explained by competition for mobile resources. I provide conditions under which initially symmetric regions realize reforms sequentially and a reform initiated in one region is afterwards adapted by another region. Forward-looking agents anticipate the policy convergence and respond less to the reform than the current difference in policies would imply.
Keywords: D78; F23; H77; 330